INO80 function is required for mouse mammary gland development, but mutation alone may be insufficient for breast cancer - Thang, Nguyen Xuan; Han, Dong Wook; Park, Chanhyeok; Lee, Hyeonji; La, Hyeonwoo; Yoo, Seonho; Lee, Heeji; Uhm, Sang Jun; Song, Hyuk; Do, Jeong Tae; Park, Kyoung Sik; Choi, Youngsok; et al. (Frontiers in Cell and Developmental Biology, 2023)
The aberrant function of ATP-dependent chromatin remodeler INO80 has been implicated in multiple types of cancers by altering chromatin architecture and gene expression; however, the underlying mechanism of the functional involvement of INO80 mutation in cancer etiology, especially in breast cancer, remains unclear. In the present study, we have performed a weighted gene co-expression network analysis (WCGNA) to investigate links between INO80 expression and breast cancer sub-classification and progression. Our analysis revealed that INO80 repression is associated with differential responsiveness of estrogen receptors (ERs) depending upon breast cancer subtype, ER networks, and increased risk of breast carcinogenesis. To determine whether INO80 loss induces breast tumors, a conditional INO80-knockout (INO80 cKO) mouse model was generated using the Cre-loxP system. Phenotypic characterization revealed that INO80 cKO led to reduced branching and length of the mammary ducts at all stages. However, the INO80 cKO mouse model had unaltered lumen morphology and failed to spontaneously induce tumorigenesis in mammary gland tissue. Therefore, our study suggests that the aberrant function of INO80 is potentially associated with breast cancer by modulating gene expression. INO80 mutation alone is insufficient for breast tumorigenesis.